Clinical response of edentulous people treated with mini dental implants in nine dental practices. (17th July 2013) - Mundt, Torsten; Schwahn, Christian; Stark, Thomas; Biffar, Reiner
<x xml:space="preserve">Abstract</x> Objectives To analyse implant survival, prosthetic aftercare and quality of life (QoL) after stabilisation of complete dentures with mini‐implants. Background Many edentulous patients refuse implant therapy due to the expenses and fear of surgery. Studies on minimally invasive and low‐cost mini‐implants remain rare. Materials and methods A total of 133 participating patients from nine private practices were evaluated via patient records, questionnaires and clinical examinations. Complications, maintenance, QoL questions and the German short version of the oral health impact profile (OHIP‐G14) were analysed. Results After 7 to 61 months, 15 of 336 maxillary implants and 11 of 402 mandibular implants had to be removed. In addition, four mandibular implants experienced fracture. The difference between the 4‐year survival rates of 94.3% for the maxilla and 95.7% for the mandible was not statistically significant (p = 0.581). All original 144 overdentures remained functional. The prosthetic interventions were typically limited to repairs of acrylic base fractures (about one in five patients), changes of plastic O‐rings and relining procedures. The participants showed OHIP‐G14 scores (median = 2) that were comparable with those of patients with overdentures retained by conventional implants. Conclusions Mini‐implant survival was similar to that of regular‐diameter implants. Although some prosthetic aftercare was necessary, none of the overdentures had to be replaced. Prospective studies comparing conventional and mini‐implants are warranted.